KNOWLEDGE AND ATTITUDE OF POLICE TRAFIC AS EMERGENCY FIRST RESPONDER - Sipayung, Normi Parida; Syapitri, Henny; Simamora, Marthalena; Sipayung, Rosetty; Sinaga, Caca Rohali (Jurnal Ilmiah Keperawatan, 2024)
Day after day, the traffic accident rate in Indonesia is increasing. Traffic accidents can result in various injuries or trauma life-threatening, such as head injury, femur fracture, open pneumothorax, flail chest and so on.  Police officer are identified as emergency first responder.  Police as first responders, at Medan Police Traffic Unit, should have good knowledge about first aid in case of accidents. Some are related to a person's knowledge, namely education, work experience and training attended. The aim of this research is to determine the relationship between knowledge and attitudes of police as emergency first responder at Medan police tropic unit. Methods in this research is quantitative using a cross sectional design, and tested using the Chi-square test. The population in this study was traffic police at Medan Police Traffic Unit, with a sample size of 40 people. The research results show that most of the respondents have a good level of knowledge (57,5%) and the majority of respondents have a good attitude (60.0%). This shows that there is a relationship between knowledge with the attitude of the traffic police as first responders. Good knowledge of traffic police about first responders in accidents really determines the attitude of the police in providing first aid in accidents. Police knowledge as emergency first responders, the majority have a good category as many as 23 people (57.5%).